Pengaruh Model Flipped Classroom dan Motivasi Belajar terhadap Keterampilan Menulis Proposal Kegiatan Siswa Kelas XI - Nola Florina; Atmazaki Atmazaki (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This study aimed to determine the effect of the flipped classroom model and learning motivation on the activity proposal writing skills of class XI high school students. The research was conducted at the UNP Laboratory Development High School with a total sample of 57 students, 27 students from the experimental class and 30 students from the control class. This type of research is quantitative research with experimental methods. The experimental design used is factorial design. The population of this study was class XI students at the UNP Laboratory Development High School who were enrolled in the 2022/2023 academic year. The research sample consisted of two classes: class XI IIS 3 and class XI IIS 4. Sampling was carried out using a purposive sample technique. The research instruments were performance tests and questionnaires. Based on research, the flipped classroom model has a significant effect on students' activity proposal writing skills, both for students who have high learning motivation and students who have low learning motivation. In addition, there is no influence between learning motivation and the flipped classroom model.